Time Factor in Territorial Disputes - Distefano, Giovanni (My University, 2018)
This chapter endeavours to tackle two major issues making up the whole problématique of time in connection with territorial disputes. Both relate to the classical dimensions of the time factor in this context and will thus be the focus of this contribution. A general remark must be made from the outset: As it will be shown hereafter, time is one of the two (factual) dimensions, alongside with space,3 within which state (and thus human) activity occurs. Consequently, public international law does not recognize time and space as vesting or divesting facts likely per se to create, extinguish or modify territorial titles. In other words, certain facts or acts performed by states must be seen against the background of time, since public international law deems them capable of extinguishing or modifying titles of territorial sovereignty.4 Grotius had already vividly grasped the true function of time as one of the dimensions of human thought and activity: ‘For though time is the great agent, by whose motion all legal concerns and rights may be measured and determined, yet it has no effectual power of itself to create an express title to any property.’